Biochemical profile of young pre- and mildly hypertensive adults: a single centre, case control study - Abdullah, Aszrin; Mohd Shah, Azarisman Shah; Abdul Razak, Tariq; Mohd Noor, Noriah (2011)
Background: Hypertension is one of the most important risk factors for Cardiovascular Disease in Malaysia. Hypertension prevalence in Malaysia is at 42.6% based on the 2006 National Health and Morbidity Survey and population-based hypertension control is extremely poor at only 26.8%.